2017
DOI: 10.2147/opth.s133594
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes in patients with branch retinal vein occlusion who received intravitreal aflibercept with or without intravitreal ranibizumab

Abstract: PurposeThe purpose of this study was to determine the short-term outcomes for patients who received intravitreal aflibercept (IVA) with or without intravitreal ranibizumab (IVR) for macular edema (ME) due to branch retinal vein occlusion (BRVO).Patients and methodsPatients received IVA for ME due to BRVO. Patients who initially received IVA were defined as the treatment-naïve group and those who were switched from IVR to IVA after ME recurrence were defined as the switching group. Patient outcomes were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…There have been many studies on the effectiveness of switching from ranibizumab to a ibercept in patients with macular edema secondary to a BRVO. The patients studied can be classi ed into two types; one type is the patient who was not responding to ranibizumab and were then switched to a ibercept, [5,9,10] and the other type was the patient who had a difference in the duration of the effectiveness between two agents as indicated by the lengthening of the interval after switching to a ibercept. [6] The di culty in comparing these results is that there is a spontaneous healing in more than 30% of cases if macular edema secondary to BRVO develops within one year after the onset of BRVO.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the effectiveness of switching from ranibizumab to a ibercept in patients with macular edema secondary to a BRVO. The patients studied can be classi ed into two types; one type is the patient who was not responding to ranibizumab and were then switched to a ibercept, [5,9,10] and the other type was the patient who had a difference in the duration of the effectiveness between two agents as indicated by the lengthening of the interval after switching to a ibercept. [6] The di culty in comparing these results is that there is a spontaneous healing in more than 30% of cases if macular edema secondary to BRVO develops within one year after the onset of BRVO.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are further supported by Wirth et al who reported that switching of treatment not only showed anatomical benefits but also a statistically significant prolongation of the retreatment interval [ 24 ]. Sakanishi et al also reported a short-term beneficial anatomic and functional outcome in patients whose treatment was converted from ranibizumab to aflibercept [ 22 ]. This study therefore aims to act as a stepping stone regarding the decision of switching of anti-VEGF therapy, with the primary aim of improving macular integrity and/or visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a limited number of studies have published data to assess the effects of switching therapies (anti-VEGF) in patients with BRVO with MO [ 22 24 ]. The purpose of this study is to add to this growing evidence of alternative treatments in patients with refractory MO secondary to BRVO, in order to gain a better understanding of the clinical effects of switching treatment from ranibizumab to aflibercept.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is hypothesized that the intravitreal injection of ranibizumab combined with argon ion laser photocoagulation has better safety and effectiveness in the treatment of different degrees of CRVO. The impairment of vision from trunk occlusion or hemi-occlusion is more serious than in branch occlusion and CRT is increased significantly, accompanied by severe local edema, bleeding, and leakage (24,25); trunk occlusion or hemi-occlusion frequently involves the distal branch vessels; although there may be more target vessels in branch occlusion, pathological changes, including ischemia and inflammation, are mild, and it has a better response to the ranibizumab combined with laser photocoagulation therapy (26,27).…”
Section: Discussionmentioning
confidence: 99%